2014
DOI: 10.1097/jto.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

TGM2: A Cell Surface Marker in Esophageal Adenocarcinomas

Abstract: Introduction Esophageal adenocarcinomas (EAC) are aggressive cancers that are increasing in incidence and associated with a poor prognosis. The identification of highly expressed genes in EAC relative to metaplastic Barrett’s esophagus (BE) may provide new targets for novel early cancer detection strategies using endoscopically administered, fluorescently labeled peptides. Methods Gene expression analysis of BE and EACs were used to identify the cell surface marker transglutaminase 2 (TGM2) as overexpressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…In addition, we recently showed TGM2 is overexpressed on the surface of EAC cells [26]. In the current study, we chose to validate CDH11, ICAM1 and CLDN3 as examples of potential cell surface markers common to subsets of both GEJAC and tEAC.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we recently showed TGM2 is overexpressed on the surface of EAC cells [26]. In the current study, we chose to validate CDH11, ICAM1 and CLDN3 as examples of potential cell surface markers common to subsets of both GEJAC and tEAC.…”
Section: Resultsmentioning
confidence: 99%
“…In the pathway analysis (Fig 5), we observed that FAM86HP has an indirect interaction with TGM2 (Transglutaminase 2), a stress-response gene [50] involved in mRNA metabolism [51] which has been reported to be upregulated during in ammation [50]. It is interesting to note that TGM2 was over expressed in individuals receiving chemo & radiation therapy, suggesting its involvement in sensitivity to radiation [52,53]. Both, TGM2 and NUPR1 ( Fig 5) have been reported to be implicated in in ammation driven primarily via the JAK/Stat and IL-17A signaling pathway [54].…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, TRIB3 might be a prognostic biomarker of acute myeloid leukemia, RHOF was overexpressed in malignant lymphomas and PAQR5 was related to ovarian cancer . In addition, in two other studies, it was indicated that TGM2 was a diagnostic signature for not only esophageal adenocarcinomas, but also for lung cancer . Furthermore, STC2 was considered to be a diagnostic gene of lung cancer, as well as a promising prognostic gene of high‐grade serous ovarian cancer .…”
Section: Discussionmentioning
confidence: 99%
“…54 In addition, in two other studies, it was indicated that TGM2 was a diagnostic signature for not only esophageal adenocarcinomas, but also for lung cancer. 55,56 Furthermore, STC2 was considered to be a diagnostic gene of lung cancer, as well as a promising prognostic gene of high-grade serous ovarian cancer. 57,58 RPH3AL may be related to the diagnosis of colorectal cancer 59 and, in another study, it was determined that…”
Section: Discussionmentioning
confidence: 99%